2016
DOI: 10.18330/jwallacea.2016.vol5iss1pp79-90
|View full text |Cite
|
Sign up to set email alerts
|

Basic Properties and Potential Uses of Saling-Saling Wood

Abstract: ABSTRAKPenelitian ini dilakukan untuk menguji sifat dasar (struktur anatomi, kimia, sifat fisis dan mekanis) kayu saling-saling (Artocarpus teysmanii Miq.) yang diambil dari hutan alam di Kabupaten Luwu Timur Provinsi Sulawesi Selatan. Potensi kegunaan kayu ditetapkan dengan mempertimbangkan sifat dasar dan penggunaan kayu tersebut oleh penduduk setempat. Hasil penelitian menunjukkan bahwa kayu saling-saling memiliki teras dan gubal jelas dapat dibedakan, gubal berwarna putih kekuningan dan teras cokelat kekun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
3
1
Order By: Relevance
“…4). These shrinkage values were slightly higher than that were reported by Lempang (2014), the tangential and radial shrinkage of red jabon wood were 5.41% and 3.03% respectively.…”
Section: Dimensional Stability Of Woodcontrasting
confidence: 69%
See 1 more Smart Citation
“…4). These shrinkage values were slightly higher than that were reported by Lempang (2014), the tangential and radial shrinkage of red jabon wood were 5.41% and 3.03% respectively.…”
Section: Dimensional Stability Of Woodcontrasting
confidence: 69%
“…Havil (red jabon) is one of the potential fast growing wood species for industrial or community plantation forests. This wood has fairly good basic wood properties with moderate density and strength (strength class III) (Lempang, 2014), but its durability is low (durability class IV) (Cahyono et al, 2015, Halawane, 2015. So quality improvement is required particularly its dimen-sional stability and durability against degrading organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The density of sengon was 0.32 g/cm 3 , and previous research reported shrinkage in radial and tangential directions of 2.5% and 5.2%, respectively (wet to dry kiln) (Iskandar 2006). Jabon, which had a density of 0.46 g/cm 3 , was previously report to have shrinkage in the radial and tangential directions of 3.03% and 5.41%, respectively (wet to dry kiln) (Lempang 2014). Width shrinkage was also affected by the type of adhesive.…”
Section: Moisture Contentmentioning
confidence: 92%
“…The best and simplest way to determine the quality is through physical features, like density. Meanwhile, wood strength is classified according to its specific gravity with flexural and compressive strength parallel to the wood fibers under air-dry conditions (Lempang 2014). Anatomical properties such as fiber length are also crucial for their suitability as pulp and paper materials.…”
Section: Introductionmentioning
confidence: 99%